Estudo fitoquímico, caracterização físico-química e avaliação da atividade antimicrobiana de Harrisia adscendens (GÜRKE) Britton & Rose (CACTACEAE) - Santos, George Luís Dias dos (2015)
Researches on medicinal plants have shown great importance to the development of new drugs. Numerous Brazilian plant species still remain without any chemical-biological study. Harrisia adscendens, Cactaceae family species found in the semi-arid northeast, is popularly known as “foxtail” and is used for treatment of "warmth", kidney problems and toothache. This study aimed to carry out phytochemical study, physicochemical characterization and biological activity of the roots of Harrisia adscendens. The plant roots were dried in an air circulating oven at a temperature of 40 ° C, and then pulverized in in a slicer. The physicochemical methods for evaluation were conducted according to the Brazilian Pharmacopoeia. The powder was submitted to the test pH, particle size, density, ash content, loss on drying and thermal analysis. Subsequently, the powder was thoroughly macerated and the filtrate concentrated on a rotary evaporator to yield the crude ethanolic extract (CEE). In phytochemical screening were made qualitative tests for identification of flavonoids, catechins, phenols / tannins, saponins and alkaloids. The antimicrobial activity was performed based minimum inhibitory concentration (MIC) against Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Candida albicans and Candida tropicalis by microdilution test plates. For isolation and identification of secondary metabolites have been used chromatographic and spectroscopic techniques such as TLCA, IR, MS, NMR 1H and 13 C 1D and 2D. In physical-chemical analysis 28.4% of the powder was held in mesh 180 µ m classifying it as semi-fine. The powder has a relatively acidic character pH of 5.68. A gross density of 0.322 g/mL, tapped density of 0.487 g/mL allowing the calculation of the Hausner factor of 1.51 was observed. The compressibility and the compressibility index were 10.5 mL and 33.8%, respectively. The percentage of residual moisture by loss on drying was 12.7% and the determination of total ash content showed 6.14% inorganic matter. In the thermal analysis, there was a loss of mass of 88% organic and 12% ash. In qualitative phytochemical screening results obtained were suggestive of the presence of alkaloids according to positive tests with Dragendorff, Bouchardat and Mayer reagent. Regarding the antimicrobial activity it was considered that all extracts fronts Staphylococcus aureus, Escherichia coli, Pseudomonas aeruginosa, Candida albicans and Candida tropicalis showed no activity. After isolation and comparisons with the literature, they were identified the 2-methyl-9H-β-carboline-2-ium (β- carboline alkaloid) and 2',4'-methoxyacetophenone-6'-dihydroxy-2'-O-β-glucose (acetophenone) substances. The physicochemical data obtained from the study showed H. adscendens information relevant to the development of new phytotherapy/phytochemical. Regarding the antimicrobial activity there is no standardization of the reference values to evaluate the antimicrobial potential of natural products from the CIM. The secondary metabolites isolated in this study are unprecedented for both Harrisia gender and for the Cactaceae family.